The Effect of Good Corporate Governance on Stock Return Volatility During The Covid 19 Pandemic on Tourism Companies Listed on The Indonesia Stock Exchange in 2019-2022 - Aliyah Aliyah; Ratih Kusumawardhani; Pristin Prima Sari (Journal of Management Economic and Financial, 2024)
This study investigates the impact of good corporate governance on stock return volatility within the context of the COVID-19 pandemic, focusing on tourism companies listed on the Indonesia Stock Exchange from 2019 to 2022. The research examines how effective corporate governance practices contribute to managing stock return volatility during this challenging period. By analyzing financial data and corporate governance indicators, the study aims to provide insights into the relationship between corporate governance and stock market dynamics in the turbulent environment brought about by the pandemic.